2016
DOI: 10.1039/c6ra01549b
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of 2,5-diformylfuran from fructose using a magnetic bi-functional catalyst

Abstract: A magnetic bi-functional WO3HO-VO(salten)-SiO2@Fe3O4nanocatalyst was prepared to directly synthesize 2,5-diformylfuran (2,5-DFF) from fructose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…It is used in the synthesis of fungicides, drugs, and polymeric materials [85]. Several promising catalytic routes for 2,5-DFF production are reported in the literature [85][86][87][88][89][90][91]. The complete transformation of 5-HMF with a 90% yield of 2,5-DFF was achieved with V 2 O 5 /TiO 2 catalyst in the presence of air and toluene or methyl isobutyl ketone (MIBK) as the solvent.…”
Section: -Hmf Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used in the synthesis of fungicides, drugs, and polymeric materials [85]. Several promising catalytic routes for 2,5-DFF production are reported in the literature [85][86][87][88][89][90][91]. The complete transformation of 5-HMF with a 90% yield of 2,5-DFF was achieved with V 2 O 5 /TiO 2 catalyst in the presence of air and toluene or methyl isobutyl ketone (MIBK) as the solvent.…”
Section: -Hmf Derivativesmentioning
confidence: 99%
“…Researchers also disclosed the potential of iron as a cheap catalyst for the production of 2,5-DFF from 5-HMF [87,88]. Mittal et al [89] reported the use of magnetic bi-functional WO 3 HO-VO (salen)-SiO 2 @Fe 2 O 3 nano-catalyst to directly synthesize 2,5-DFF from fructose. In this work, an 82% yield of 5-HMF was obtained in 1 h and if a co-oxidant (H 2 O 2 ) was added, 71% 2,5-DMF was synthesized after 15 h in the presence of ambient air.…”
Section: -Hmf Derivativesmentioning
confidence: 99%
“…Graphene oxide used as a highly active catalyst for one‐pot conversion of fructose to DFF . A magnetic nanocatalyst bi‐functional WO 3 HO‐VO (Salten)‐SiO 2 @Fe 3 O 4 was used to directly synthesize DFF from fructose with the addition of H 2 O 2 as co‐oxidant . A highly active V‐containing all‐silica beta (VSi‐Beta) zeolite for the one‐pot and one‐step conversion of various carbohydrates into DFF with sulfuric acid as co‐catalyst and atmospheric oxygen .…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of carbohydrates to platform compounds such as 5-(hydroxymethyl) furfural (HMF), [6][7][8][9][10] furfural, [11][12][13] levulic acid (LA) 14,15 and the utilization of platform compounds have both been extensively researched. Furfuryl alcohol, [16][17][18][19][20] tetrahydrofurfuryl alcohol, 21,22 dimethylfuran, 23 2,5-furandicarboxylic acid, 24 diformylfuran, [25][26][27][28][29][30][31] cyclopentanone, 32,33 g-valerolactone, 14,[34][35][36] and tetrahydro-2,5-furandimethanol 37,38 are the typical target products.…”
Section: Introductionmentioning
confidence: 99%